Pathogenicity and transmissibility of novel influenza viruses - Ma, Jingjiao (Kansas State University, 2015)
Influenza A virus (IAV) is an enveloped, segmented, negative-sense RNA virus that infects avian species and mammals. Its segmented feature enables antigenic shift which can generate novel IAVs that pose a threat to animal and public health due to lack of immunity to these viruses. Pigs have been considered the “mixing vessels” of influenza A viruses to generate novel reassortant viruses that may threaten animal and public health. Therefore, it is necessary to understand the pathogenicity and transmissibility of newly emerged reassortant viruses in swine. Adding to this complexity is the newly identified bat influenza A-like viruses which have roused interest in understanding the evolutionary history and pandemic potential of bat influenza. At least 10 different genotypes of novel reassortant H3N2 IAVs with gene(s) from 2009 pandemic H1N1 [A(H1N1)pdm09] have been identified in pigs in the United States. To date, only three genotypes of these viruses have been evaluated in animal models leaving the pathogenicity and transmissibility of the other seven genotype viruses unknown. We showed that reassortant viruses with genes from A(H1N1)pdm09 are pathogenic and transmissible in pigs. Further studies showed that avian-like glycine at position 228 of the HA receptor binding site is responsible for inefficient transmission of the reassortant H3N2 IAV with five A(H1N1)pdm09 genes. Studying the recently discovered IAV-like sequences from bats has been hindered by the lack of live virus isolation or culturing. Using synthetic genomics, we successfully rescued modified bat influenza viruses that had the HA and NA coding regions replaced with two classical IAVs. Additional studies were performed with truncations on NS1 protein and substitution of a putative virulence mutation in bat influenza PB2. Virus reassortment experiments demonstrated that bat influenza has limited genetic and protein compatibility with other influenza viruses; however, it readily reassorts with another divergent bat influenza virus. Taken together, our results provide insights into the pathogenicity and transmissibility of novel reassortant H3N2 IAVs in pigs. It also indicates that the bat influenza viruses recently identified are viable viruses that pose little pandemic threat to humans. Moreover, they provide new insights into the evolution and basic biology of influenza viruses.
Keywords: Pathogenicity; Transmissibility; Novel; Bat influenza; Swine influenza; Epidemiology (0766); Veterinary Medicine (0778); Virology (0720)